Anti-inflammatory effects of aqueous extract from Dichroa febrifuga root in rat liver. - Cho Byung Tae; Lee Jun Hyuk; Ko Woo Shin; Kim Young Hee; Choi Yung-Hyun; Kang Ho-Sung; Kim Han-Do (Acta Pharmacologica Sinica, 2016)
AIM: To study the anti-inflammatory effects of aqueous extract from Dichroa febrifuga root (AEDF) for suppression in the process of lipopolysaccharide (LPS)-induced sepsis in the rat liver. METHODS: The inhibitory effect of AEDF on the alteration of inflammatory proteins was investigated by Western blot and immunohistochemical analysis. RESULTS: Western blot analysis showed that the level of nuclear factor (NF)-kappaBp65 was markedly up-regulated and (I)-kappaBalpha was down-regulated by LPS (8 mg/kg) challenge. However, AEDF 100 mg/kg inhibited induction of NF-kappaBp65 and degradation of I-kappaBalpha in the liver of LPS-challenged rats. Immunohistochemical analysis showed that while the expression of the NF-kappaBp65, tumor necrosis factor (TNF)-alpha and inducible nitric oxide synthase (iNOS) tended to increase, that of I-kappaBalpha was decreased in the hepatocytes of rats challenged with LPS. A slight decline of NF-kappaBp65, TNF-alpha and iNOS, but an increase of I-kappaBalpha were observed in the hepatocytes of the rats pretreated with AEDF. CONCLUSION: AEDF may act as a therapeutic agent for inflammatory disease through a regulation of inflammation-related proteins.